Computer‐aided mathematical modeling and numerical simulation and theoretical analysis of the polypropylene polymer air drawing in spunbonding nonwoven process. Issue 2 (7th October 2013) - Bo, Zhao
<x xml:space="preserve">Abstract</x> In this article, as a nonlinear mathematical problem, the air‐drawing model and the air jet flow field model of the polymer during spunbonding process are also presented, because the continuous filament fiber not always occurs in the spunbonding process, therefore, there exists the filament fiber breakage, the broken fibers occur in the flow field of spunbonding process is a two‐phase flow problem, we suggested a new model called the sphere–spring model that can best described the broken fibers movement features. At the same time, the air‐drawing model of the polypropylene polymer in a spunbonding process is presented and solved by introducing the numerical computation results of the air jet flow field of aerodynamic device. The model's predictions of the filament fiber diameters, crystallinities, and birefringences are coincided well with the experimental data. The effects of the processing parameters on the filament fiber diameter are discussed. A lower polymer throughput rate, lower quench air temperature, higher polymer melt initial temperature, higher air initial temperature, higher air initial speed, medium smaller venturi gap, higher air suction speed, higher quench air pressure, higher air suction speed, higher extrusion temperature, higher quench air pressure, higher cooling air temperature, and so on can all produce finer filament fiber. The results show great prospects for this research in the field of computer‐assisted design of spunbonding technology. POLYM. ENG. SCI., 54:481–492, 2014. © 2013 Society of Plastics Engineers